2015
DOI: 10.1002/glia.22853
|View full text |Cite
|
Sign up to set email alerts
|

Aquaporin-4 regulates the velocity and frequency of cortical spreading depression in mice

Abstract: The astrocyte water channel aquaporin-4 (AQP4) regulates extracellular space (ECS) K+ concentration ([K+]e) and volume dynamics following neuronal activation. Here, we investigated how AQP4-mediated changes in [K+]e and ECS volume affect the velocity, frequency and amplitude of cortical spreading depression (CSD) depolarizations produced by surface KCl application in wild-type (AQP4+/+) and AQP4-deficient (AQP4−/−) mice. Contrary to initial expectations, both the velocity and frequency of CSD were significantl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
43
4

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(48 citation statements)
references
References 55 publications
1
43
4
Order By: Relevance
“…Of note, the osmotic stimuli necessary to evoke calcium transients downstream of AQP4 activation in earlier studies (Benfenati et al, ; Jo et al, ; Mola et al, ; Thrane et al, ) were considerably stronger than the ones induced in our study. Interestingly, it was recently shown that the DC potential amplitude (Thrane et al, ) and the threshold (Yao et al, ) of normoxic spreading depression are reduced in Aqp4–/– mice, indicating profound but incompletely understood differences between the mechanisms underlying spreading depolarizations in the healthy and ischemic brain. Finally, we did not detect significant differences in PID‐induced edema of astrocytes in Aqp4–/– compared with wildtype mice, indicating that aquaporins may not contribute to the level of cell swelling in astrocytes, similarly to what has been reported for neurons (Steffensen, Sword, Croom, Kirov, & MacAulay, ).…”
Section: Discussionmentioning
confidence: 99%
“…Of note, the osmotic stimuli necessary to evoke calcium transients downstream of AQP4 activation in earlier studies (Benfenati et al, ; Jo et al, ; Mola et al, ; Thrane et al, ) were considerably stronger than the ones induced in our study. Interestingly, it was recently shown that the DC potential amplitude (Thrane et al, ) and the threshold (Yao et al, ) of normoxic spreading depression are reduced in Aqp4–/– mice, indicating profound but incompletely understood differences between the mechanisms underlying spreading depolarizations in the healthy and ischemic brain. Finally, we did not detect significant differences in PID‐induced edema of astrocytes in Aqp4–/– compared with wildtype mice, indicating that aquaporins may not contribute to the level of cell swelling in astrocytes, similarly to what has been reported for neurons (Steffensen, Sword, Croom, Kirov, & MacAulay, ).…”
Section: Discussionmentioning
confidence: 99%
“…The effective involvement of astrocytic buffering in SD management was proven by deleting aquaporin-4 channels, or hindering glutamate clearance. As such, the genetic knock-out of aquaporin-4 channels in mice decreased the rate of the K + surge and K + reuptake with SD, in association with a slower rate of SD propagation, and lower SD frequency (Yao et al, 2015). On the other hand, EAAT2-mediated glutamate clearance hampered in the absence of the α2 subunit of the astrocytic Na + /K + ATPase was associated with the facilitation of SD initiation (Capuani et al, 2016).…”
Section: Recovery From Sdmentioning
confidence: 99%
“…Each K þ -selective microelectrode was calibrated in standard solutions of known K þ concentrations (1, 3, 5, 10, 30, 50 and 100 mM) (Figure 3(a)). 33 In each experiment, a K þ -sensitive microelectrode was lowered into the cortex, together with another microelectrode (outer tip diameter ¼ 20 mm) filled with 150 mM NaCl and 1 mM HEPES to serve as reference and acquire DC potential (<1Hz). An Ag/AgCl electrode implanted under the skin of the animal's neck was used as common ground.…”
Section: Electrophysiologymentioning
confidence: 99%